Cheap Talk With Transparent Motives - Lipnowski, Elliot; Ravid, Doron (Econometrica, 2020)
We study a model of cheap talk with one substantive assumption: The sender's preferences are state independent. Our main observation is that such a sender gains credibility by degrading self‐serving information. Using this observation, we examine the sender's benefits from communication, assess the value of commitment, and explicitly solve for sender‐optimal equilibria in three examples. A key result is a geometric characterization of the value of cheap talk, described by the quasi concave envelope of the sender's value function.